2019
DOI: 10.1111/exd.13982
|View full text |Cite
|
Sign up to set email alerts
|

CCL3, IL‐7, IL‐13 and IFNγ transcripts are increased in skin's biopsy of systemic sclerosis

Abstract: Although several cytokines and chemokines have been investigated as possible mediators of fibrosis in systemic sclerosis (SSc), specific correlation between cytokines and organ involvement have not been found yet, and a cytokine profile characteristic of SSc is far to be identified. We studied the profile of antifibrotic and profibrotic transcripts involved in skin of SSc patients. The mRNA expression was detected by fluorescence‐based quantitative real‐time PCR (qPCR) in skin's biopsies from 14 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…IL-13 (upregulated by HCMV > 21 fold) has been shown to play a role in many inflammatory and fibrotic diseases, including SSc, and appears to be necessary in the effector phase of inflammation and fibrosis [ 72 , 73 ]. In particular, IL-13 is significantly expressed in skin biopsies of SSc patients and its levels were found markedly increased in parallel with the progression of cutaneous fibrosis in bleomycin-induced SSc murine model [ 74 , 75 ]. CCL2, CCL11, and SERPINA1 transcripts were also upregulated by HCMV (up to 39, 43, and 22 fold, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-13 (upregulated by HCMV > 21 fold) has been shown to play a role in many inflammatory and fibrotic diseases, including SSc, and appears to be necessary in the effector phase of inflammation and fibrosis [ 72 , 73 ]. In particular, IL-13 is significantly expressed in skin biopsies of SSc patients and its levels were found markedly increased in parallel with the progression of cutaneous fibrosis in bleomycin-induced SSc murine model [ 74 , 75 ]. CCL2, CCL11, and SERPINA1 transcripts were also upregulated by HCMV (up to 39, 43, and 22 fold, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…CCL3 (upregulated by HCMV > 48 fold) has been demonstrated to play a role in dermal and pulmonary fibrosis in a murine sclerodermatous disease model [ 81 ] and, recently, CCL3 transcripts were found increased in skin biopsies of SSc patients [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors report that intradermal RS‐504393 significantly lowers indicators of skin fibrosis, including myofibroblast numbers, collagen synthesis and TGFβ1 levels. Another study by Henderson et al 55 report that levels of DKK1, a negative regulator of WNT signalling, become reduced in skin biopsies as well as in fibroblasts from patients with systemic sclerosis, a chronic autoimmune disorder manifested by activation of contractile myofibroblasts and excessive ECM deposition 56–58 . Authors also report that DKK1 expression in systemic sclerosis fibroblasts is under the control of miR33a‐3p.…”
Section: Scarring Disorders Of the Skinmentioning
confidence: 99%
“…The imbalance and dysfunction of Th17/Treg cells are crucial to the generation of SSc (168). Quantitative analysis of Th17 cytokines in lesional skin of SSc showed that the expression of IL-17A, IL-13, IL-22, and IL-26 mRNA are higher compared with healthy control (169,170). The levels of circulating Th17 cells and IL-17 elevated in serum of patients with SSc.…”
Section: Systemic Sclerosismentioning
confidence: 99%